Analisis Strategi Bauran Pemasaran Produk Hortikultura pada CV. GS Organik - Werang, Agnesta Angeline; Fanggidae, Ronald P. C; Aman, Dominikus K. T; Fanggidae, Apriana H. J (Lembaga Yasin AlSys, 2025)
This study is motivated by the rising trend of organic farming in Indonesia and the importance of effective marketing strategies in this sector. This research aims to analyze the marketing mix (4P) strategies implemented by CV. GS Organik, a leading organic horticulture company in Kupang, NTT, as well as to identify the strengths, weaknesses, opportunities, and threats (SWOT) that affect their marketing performance. This study employs a qualitative method, with data collected through interviews and observations at CV. GS Organik. The research results indicate that CV. GS Organik leverages product quality, competitive pricing, strategic distribution, and diverse promotional activities to maintain a strong market position. This study concludes that a balanced marketing mix and the utilization of strengths and opportunities are crucial for sustainable growth in the organic farming sector. The implications of this research provide valuable insights for actors in organic agriculture, emphasizing the importance of targeted marketing strategies and SWOT analysis to enhance competitiveness and market reach.